Rural-Urban Determinants of Receiving Skilled Birth Attendants among Women in Bangladesh: Evidence from National Survey 2017-18 - Sohani Afroja; Abu Saleh Muhammad Nasim; Md. Salauddin Khan; Mohammad Alamgir Kabir (International Journal of Clinical Practice)
Background. SBAs (skilled birth attendants) play a crucial role in reducing maternal mortality. The proportion of maternal healthcare in Bangladesh that receives quality care at birth has increased; the reasons for this are unknown. The purpose of this study is to see if there has been a change in the use of specific maternal healthcare indicators in urban and rural areas, as well as significant risk factors. Materials and Methods. The data set was extracted from a nationally representative survey based on a cross-sectional study, the Bangladesh Health and Demographic Survey (BDHS) 2017-18. The frequency distribution reveals the general state of SBAs. To identify the association, we performed the chi-square test. Finally, multiple logistic regression was used to analyse the factors associated with SBAs and determine the degree of SBAs disparity between urban and rural areas. Results. In Bangladesh, 53% of women received SBAs during childbirth, with urban and rural areas receiving 68.1 and 52.2 percent, respectively. Women with secondary (AOR: 1.79, CI: 1.05–3.08) and higher (AOR: 4.18, CI: 2.09–8.50) education were more likely to receive SBAs than women in urban areas who were illiterate. Husband’s education, women’s working status, wealth index, children’s birth order, and number of ANC visit are significant factors in receiving SBSs in both urban and rural areas. Higher educated husbands are 1.83 times (AOR = 1.83, CI: 1.04–3.25, p = 0.037) and 1.82 times (AOR = 1.82, CI: 1.29–2.59, p = 0.001) more likely to attend skilled births than uneducated husbands in both urban and rural areas. Respondents from the richest families are more likely to attend skilled births than those from the poorest families in both urban and rural areas. Conclusion. During delivery, significant risk factors are substantially related to SBAs. More attention must be given to rural and illiterate populations, who are less likely to obtain these services, to minimize maternal and neonatal mortality. Special programs could be developed to raise awareness and facilitate the poor in receiving the basic necessities of maternal care.